2020
DOI: 10.3389/fpsyg.2020.584567
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths Predict an Increase in Mental Health and Subjective Well-Being Over a One-Month Period During the COVID-19 Pandemic Lockdown

Abstract: This study examines whether character strengths predict resilience (operationalized as stable or higher mental health and subjective well-being despite an adverse event) over a period of approximately 1 month during the COVID-19 pandemic lockdown in Spain. Using a longitudinal design, participants (N = 348 adults) completed online measures of sociodemographic data, information regarding their situation in relation to the COVID-19, character strengths, general mental health, life satisfaction, positive affect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 58 publications
1
32
1
2
Order By: Relevance
“…Most of the GRRs reported in the literature thus far are of a psychological or social nature. For example, character strengths-such as the innate ability to withstand adversity or to maintain good interpersonal relationships-have been associated with better mental health and well-being during a COVID-19-related lockdown (Martinez-Marti et al, 2020). The use of coping strategies that focus more on problem-solving was associated with reduced psychological distress in nurses exposed to an increased workload during the pandemic (Lorente et al, 2020).…”
Section: Evidence For the Relevance Of Salutogenic Factors During The Covid-19 Pandemicmentioning
confidence: 99%
“…Most of the GRRs reported in the literature thus far are of a psychological or social nature. For example, character strengths-such as the innate ability to withstand adversity or to maintain good interpersonal relationships-have been associated with better mental health and well-being during a COVID-19-related lockdown (Martinez-Marti et al, 2020). The use of coping strategies that focus more on problem-solving was associated with reduced psychological distress in nurses exposed to an increased workload during the pandemic (Lorente et al, 2020).…”
Section: Evidence For the Relevance Of Salutogenic Factors During The Covid-19 Pandemicmentioning
confidence: 99%
“…For example, a study indicated that meaningful living had a positive predictive effect on resilience and positive affect, as well as a negative predictive value on psychological health challenges and negative affect on the psychological health of young adults in the context of the pandemic (Arslan et al, 2020 ). Martínez-Martí et al ( 2020 ) evaluated the trait strengths of the general Spanish population at two points throughout the pandemic, noting that all character strength factors at point #1 correlated positively with life satisfaction and positive affect, and negatively with negative affect and poor mental health at point #2. In the health context of the pandemic, a nurse's sample (Sun et al, 2020 ) found self-coping styles included altruistic acts, team support, rational cognition, increased affection and gratefulness, development of professional responsibility, and self-reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Zest gives people the strength to work even under harsh conditions [26], such as quarantine, where people had to adapt to a new reality [45]. Hope positively predicted engagement, as it is a strength that gives people motivation for the future [46] because hope makes people more able to cope with the loss of their loved ones and more generally, to cope with disappointment and difficulties [47]. Persistence enhances engagement through the effort it applies to overcoming cognitive challenges [48] and to finishing every activity that one starts [20], which is more difficult in quarantine due to the various restrictions [45].…”
Section: The Relationships Between Character Strengths and The Engagement Component Of Wellbeingmentioning
confidence: 99%
“…Creativity positively predicted engagement by considering new and productive ways to do things and curiosity by making ongoing experiences more interesting [20]. Especially, in a new, unexpected, and crucial period such as pandemics and quarantine, strengths such as creativity and curiosity were found to be extremely useful for people to cope with their new everyday life because they had to come up new ways of living, working, and entertaining themselves [46]. Appreciation of beauty is correlated with engagement by noticing skilled performance in all domains of life [20], as engagement is correlated to fulfillment, a strength such as appreciation of beauty could facilitate a much better adjustment to the requests of the environment.…”
Section: The Relationships Between Character Strengths and The Engagement Component Of Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation